Sequencing and Analysis of the Complete Organellar Genomes of Prototheca wickerhamii - Bakuła, Zofia; Gromadka, Robert; Gawor, Jan; Siedlecki, Paweł; Pomorski, Jan J.; Maciszewski, Kacper; Gromadka, Agnieszka; Karnkowska, Anna; Jagielski, Tomasz (Frontiers in Plant Science, 2020)
Of the Prototheca genus, Protothecawickerhamii has the highest clinical significance in humans. However, neither nuclear nor organellar genomes of this species were sequenced until now. The hitherto determined and analyzed mitochondrial and plastid genomes of the alleged P. wickerhamii species belong in fact to another species, recently named Prototheca xanthoriae. This study provides a first insight into the organellar genomes of a true P. wickerhamii (type strain ATCC 16529). The P. wickerhamii mitochondrion had a 53.8-kb genome, which was considerably larger than that of Protothecaciferrii (formerly Prototheca zopfii gen. 1) and Prototheca bovis (formerly Prototheca zopfii gen. 2), yet similarly functional, with the differences in size attributable to a higher number of introns and the presence of extra unique putative genes. The 48-kb plastid genome of P. wickerhamii, compared to autotrophic Trebouxiophyceae, was highly reduced due to the elimination of the photosynthesis-related genes. The gene content of the plastid genome of P. wickerhamii was, however, very similar to other colorless Prototheca species. Plastid genome-based phylogeny reinforced the polyphyly of the genus Prototheca, with Helicosporidium and Auxenochlorella branching within clades of Prototheca species. Phylogenetic reconstruction also confirmed the close relationship of P. wickerhamii and P. xanthoriae, which is reflected in the synteny of their organellar genomes. Interestingly, the entire set of atp genes was lost in P. wickerhamii plastid genome while being preserved in P. xanthoriae.